Direct Nkx2-5 Transcriptional Repression of Isl1 Controls Cardiomyocyte Subtype Identity. (24th March 2015) - Dorn, Tatjana; Goedel, Alexander; Lam, Jason T.; Haas, Jessica; Tian, Qinghai; Herrmann, Franziska; Bundschu, Karin; Dobreva, Gergana; Schiemann, Matthias; Dirschinger, Ralf; Guo, Yanchun; Kühl, Susanne J.; et al.
Abstract : During cardiogenesis, most myocytes arise from cardiac progenitors expressing the transcription factors Isl1 and Nkx2-5. Here, we show that a direct repression of Isl1 by Nkx2-5 is necessary for proper development of the ventricular myocardial lineage. Overexpression of Nkx2-5 in mouse embryonic stem cells (ESCs) delayed specification of cardiac progenitors and inhibited expression of Isl1 and its downstream targets in Isl1 + precursors. Embryos deficient for Nkx2-5 in the Isl1 + lineage failed to downregulate Isl1 protein in cardiomyocytes of the heart tube. We demonstrated that Nkx2-5 directly binds to an Isl1 enhancer and represses Isl1 transcriptional activity. Furthermore, we showed that overexpression of Isl1 does not prevent cardiac differentiation of ESCs and in Xenopus laevis embryos. Instead, it leads to enhanced specification of cardiac progenitors, earlier cardiac differentiation, and increased cardiomyocyte number. Functional and molecular characterization of Isl1-overexpressing cardiomyocytes revealed higher beating frequencies in both ESC-derived contracting areas and Xenopus Isl1-gain-of-function hearts, which associated with upregulation of nodal-specific genes and downregulation of transcripts of working myocardium. Immunocytochemistry of cardiomyocyte lineage-specific markers demonstrated a reduction of ventricular cells and an increase of cells expressing the pacemaker channel Hcn4. Finally, optical action potential imaging of single cardiomyocytes combined with pharmacological approaches proved that Isl1 overexpression in ESCs resulted in normally electrophysiologically functional cells, highly enriched in the nodal subtype at the expense of the ventricular lineage. Our findings provide an Isl1/Nkx2-5-mediated mechanism that coordinately regulates the specification of cardiac progenitors toward the different myocardial lineages and ensures proper acquisition of myocyte subtype identity. Stem Cells 2015;33:1113–1129